Studying the Interplay Between Apolipoprotein E and Education on Cognitive Decline in Centenarians Using Bayesian Beta Regression - Xiang, Qingyan; Andersen, Stacy Lynn; Perls, Thomas T.; Sebastiani, Paola (Frontiers in Genetics, 2021)
Apolipoprotein E (APOE) is an important risk factor for cognitive decline and Alzheimer’s disease in aging individuals. Among the 3 known alleles of this gene: e2, e3, and e4, the e4 allele is associated with faster cognitive decline and increased risk for Alzheimer’s and dementia, while the e2 allele has a positive effect on longevity, and possibly on preservation of cognitive function. Education also has an important effect on cognition and longevity but the interplay between APOE and education is not well-characterized. Previous studies of the effect of APOE on cognitive decline often used linear regression with the normality assumption, which may not be appropriate for analyzing bounded and skewed neuropsychological test scores. In this paper, we applied Bayesian beta regression to assess the effect of APOE alleles on cognitive decline in a cohort of centenarians with longitudinal assessment of their cognitive function. The analysis confirmed the negative association between older age and cognition and the beneficial effect of education that persists even at the extreme of human lifespan in carriers of the e3 allele. In addition, the analysis showed an association between APOE and cognition that is modified by education. Surprisingly, an antagonistic interaction existed between higher education and APOE alleles, suggesting that education may reduce the positive effect of APOE e2 and increase the negative effect of APOE e4 at extreme old age.